Hubungan Self-Concept, Self-Disclosure dengan Kecemasan Sosial pada Remaja Korban Bullying Verbal - Devina Eka Puteri; Ulfa Danni Rosada; Caraka Putra Bhakti; Rohmatus Naini (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to determine the relationship between self-concept and self-disclosure with social anxiety among adolescents who experience verbal bullying. This research employed a quantitative approach with a correlational design. The study sample consisted of 122 junior high school students from “X” School, selected using purposive sampling based on the criterion that they had experienced verbal bullying. The instruments used included a self-concept scale, a self-disclosure scale, and a social anxiety scale, all of which had been tested for validity and reliability to ensure their suitability as research measurement tools. Data analysis was conducted using multiple correlation to examine the relationships among the variables. Partial test results showed that self-concept had a significance value of .000 (< .05), indicating a significant negative relationship between self-concept a  nd social anxiety among adolescents who experienced verbal bullying. This means that the higher the self-concept possessed by adolescents who experienced verbal bullying, the lower their level of social anxiety. Meanwhile, self-disclosure had a significance value of .542 (> .05), indicating that self-disclosure does not have a significant relationship with social anxiety among adolescents who experience verbal bullying. Simultaneously, the results of the multiple correlation analysis showed a Sig. F Change value of .001 (< .05), meaning that self-concept and self-disclosure together have a significant relationship with social anxiety. These findings indicate that although self-disclosure does not significantly relate to social anxiety when examined individually, when viewed simultaneously alongside self-concept, both variables contribute to variations in social anxiety among adolescents who experience verbal bullying.